Chemical Profiling, Antioxidant, and Antiproliferative Activities of Algerian Cistus creticus L. Leaf Extracts: Evidence from In Vitro and In Silico Studies - Aouiffat, Yacine; Benaceur, Farouk; Bakchiche, Boulanouar; Kadi, Imededdine; Berrabah, Fathi; Gouzi, Hicham; Bardaweel, Sanaa K.; Shakya, Ashok K.; Mohamed, Asmaa S.; Ghareeb, Mosad A. (Current Topics in Medicinal Chemistry, 2025)
BackgroundResearch into oxidative stress, cancer, and natural products revealed promising avenues for therapeutic intervention. Natural products are considered potent pharmaceuticals in combating oxidative stress and its relationship with cancer.MethodsThis study was carried out to evaluate the chemical profile and antioxidant activities using DPPH, ABTS, Phenanthroline, Cupric, Phosphomolybdenum, FRAP, Hydroxyl, Iron chelation in vitro assays, and anticancer properties by MTT method of Cistus creticus extracts. The chemical composition was determined using the LC-MS/MS technique. Therefore, in silico methods, particularly molecular docking and dynamic simulation were applied for molecular interaction analysis.ResultsThe obtained results revealed a wide variety of phenolic compounds in all studied fractions, in their qualitative and quantitative distribution. In most antioxidant assays, the butanol and ethyl acetate extracts exhibited the most effective effects, followed by the aqueous extract, while the petroleum ether and chloroform fractions exhibited much lower activity in comparison with standards. In parallel, ethyl acetate, n-butanol, and chloroform extracts exhibited potent antiproliferative activity against T47D and A549 cell lines, while the aqueous extract showed an IC50 in the range of mg/ml. Moreover, the analysis of interactions identified compounds against particular targets in studied cell lines using molecular docking showed a great affinity, especially for the ligands Hesperidin, Luteolin-7-O-glucoside and Rutin. Also, the molecular dynamic simulation of the interacting complexes Hesperidin-mTOR, Rutin-EGFR and Apigenin-HER2 revealed precise interaction, providing insights into their stability and dynamic behavior. Furthermore, the studied ligand exhibited interesting pharmacokinetic properties with no reported toxicity.ConclusionThese findings confirmed the potential of Algerian Cistus creticus L. leaf extracts as promising therapeutic molecules for combating oxidative stress and cancer.
Keywords: Molecular modeling